Islamic civilization and liberation transformations in (Journal of the College of Basic Education, 2026)
The designs that are taken from the Islamic style characterize them as a distinctive feature as a beautiful art. The interior designer can touch the aspects of this art in the types of modern interior designs that link the past to the present according to the perspective of technological development. And in accordance with the specificity of the subject of the research consists of four chapters. The first chapter in the formulation of the problem of research, which is summarized shortfalls in the recruitment of Islamic style in the interior spaces of modern commercial centers in Baghdad. The importance of the research in a statement enriched the scientific material of students of the Faculty of Fine Arts and the corresponding disciplines and other colleges and adds the addition of descriptive knowledge added to the messages and the papers completed at the college and the research objective is to (detect the lack of the use of Islamic style in the interior spaces in modern business centers). The limits of the objective researc (the study of the design transformations of the Islamic model in the interior spaces of the commercial centers) and the temporal limits were the date of the construction of the bazaar (2017) and the spatial boundaries (the spaces of the Babillon Bazaar Mall of Mansour / Baghdad / Karkh). The research also dealt with the definition of many terms related to the subject of research. While the second chapter includes both previous studies and the theoretical framework. In the theoretical framework in the second chapter there is a study of two subjects: the first topic (style developments in Islamic design) and the second part (the formal transformations of the contemporary Islamic models). Chapter 3 referred to the procedures Research, where it adopted the Babilon Bazaar Bazaar the research community has been selected three models of the intended samples of their spaces as described and analyzed . The fourth chapter included a discussion of a number of results within the main axes achieved the research objective, which reached the research study the most important . To achieve style According to the age and taki And the first sample is achieved and is achieved relatively in the second sample. The results of the research reached a number of conclusions, the most important of which are: - The specificity of the vocabulary and elements of the Islamic style and its use within the internal spaces influenced the appearance of the model and its adaptation and evolution over time and to connect the past with the present and preserve the symbolism And the identity of the Islamic model. The creativity in the Islamic designs depends on the experience of the interior designer in the best choice of vocabulary and design units suitable within the harmonious effects such as the types of materials, furniture, furniture and overlapping overlapping between geometric an vegetal decoration and embossed and embossed and according to their location within the internal space